2007
DOI: 10.1172/jci32338
|View full text |Cite
|
Sign up to set email alerts
|

The iron chelator deferasirox protects mice from mucormycosis through iron starvation

Abstract: Mucormycosis causes mortality in at least 50% of cases despite current first-line therapies. Clinical and animal data indicate that the presence of elevated available serum iron predisposes the host to mucormycosis. Here we demonstrate that deferasirox, an iron chelator recently approved for use in humans by the US FDA, is a highly effective treatment for mucormycosis. Deferasirox effectively chelated iron from Rhizopus oryzae and demonstrated cidal activity in vitro against 28 of 29 clinical isolates of Mucor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
274
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 288 publications
(294 citation statements)
references
References 43 publications
10
274
2
Order By: Relevance
“…On the contrary, deferasirox demonstrates cidal activity against Mucorales in vitro and treatment of Rhizopus-infected mice with deferasirox markedly improves survival, reduces fungal burden in target organs, and enhances the host inflammatory response to mucormycosis, further reinforcing the role of iron in pathogenesis. 1 These results were also corroborated by our findings that deferasirox protects Drosophila from mucormycosis infection. 6 Fu et al 7 cloned the high-affinity iron permease (FTR1) of R. oryzae, which is a primary effector for organism ability to acquire iron in iron-limited environments such as those found in susceptible hosts.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…On the contrary, deferasirox demonstrates cidal activity against Mucorales in vitro and treatment of Rhizopus-infected mice with deferasirox markedly improves survival, reduces fungal burden in target organs, and enhances the host inflammatory response to mucormycosis, further reinforcing the role of iron in pathogenesis. 1 These results were also corroborated by our findings that deferasirox protects Drosophila from mucormycosis infection. 6 Fu et al 7 cloned the high-affinity iron permease (FTR1) of R. oryzae, which is a primary effector for organism ability to acquire iron in iron-limited environments such as those found in susceptible hosts.…”
Section: Introductionsupporting
confidence: 78%
“…All of these factors contribute to higher mortaility in patients with mucormycosis and make the results of this small pilot trial hard to interpret. 17 Only a large, Phase III trial, potentially enrolling only diabetic or corticosteroid-treated patients (since animal model and case studies suggested a benefit of using deferasirox in this patient populations), 1,18 and excluding cancer/neutropenia patients, could further elucidate the safety and efficacy of initial, adjunctive deferasirox for the treatment of mucormycosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations